2005
DOI: 10.1207/s15327914nc5301_4
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of Selected Nutrients, Foods, and Phytochemicals and Prostate Cancer Risk in Western New York

Abstract: A number of epidemiological studies have suggested that diet may affect the etiology of prostate cancer, but few have investigated the impact of phytochemical intakes on this cancer. We conducted a case-control study of diet and prostate cancer in western New York involving 433 men with primary, histologically confirmed prostate cancer and 538 population-based controls, frequency matched to cases on age and county of residence. Diet was assessed with a detailed food-frequency questionnaire. We calculated daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 21 publications
5
99
0
1
Order By: Relevance
“…The Health Professionals Follow-up Study, a cohort study of dietary lycopene with almost 2,500 cases (16), observed an inverse association, whereas no association was found in two other cohorts (17,41), including our study of >1,300 cases in the PLCO (17,(42)(43)(44)(45)(46). Among serum-based studies of circulating lycopene (22-26, 29, 47), the Physicians' Health Study reported that high lycopene concentrations were associated with lower risk of aggressive prostate cancer in the subgroup of men randomized to the placebo arm only (22).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The Health Professionals Follow-up Study, a cohort study of dietary lycopene with almost 2,500 cases (16), observed an inverse association, whereas no association was found in two other cohorts (17,41), including our study of >1,300 cases in the PLCO (17,(42)(43)(44)(45)(46). Among serum-based studies of circulating lycopene (22-26, 29, 47), the Physicians' Health Study reported that high lycopene concentrations were associated with lower risk of aggressive prostate cancer in the subgroup of men randomized to the placebo arm only (22).…”
Section: Discussionmentioning
confidence: 51%
“…Some questionnaire-based case-control studies (42,43,45,(53)(54)(55)(56) reported lower prostate cancer risks with high intake of h-carotene, however, other studies, including five cohort studies (13,41,46,53,(57)(58)(59)(60)(61)(62)(63)(64)(65), did not. In bloodbased observational studies, some showed no relation between h-carotene concentrations and prostate cancer (23,24,26,32), whereas similar to ours, three studies (24,25,28) found increased risks, of which one was significant in blacks (28).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of dietary intake and blood level studies have indicated no association with prostate cancer risk of folate, vitamin B6, methionine, and homocysteine (8)(9)(10)(11)(12)(13)(14)(15)(16). A recent study reported a positive association between folic acid supplementation and prostate cancer risk (17).…”
Section: Introductionmentioning
confidence: 99%
“…The emerging studies on cancer prevention and treatment with natural products expand the traditional treatment of prostate cancer (1). Curcuminoids are phenolic coloring compounds that can be extracted from the rhizomes of Curcuma longa linn.…”
Section: Introductionmentioning
confidence: 99%